2009
DOI: 10.5194/angeo-27-1047-2009
|View full text |Cite
|
Sign up to set email alerts
|

TEC variations during low solar activity period (2005–2007) near the Equatorial Ionospheric Anomaly Crest region in India

Abstract: Abstract.The dual frequency signals from the GPS satellites recorded at Rajkot (22.29 • N, 70.74 •

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
126
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 221 publications
(145 citation statements)
references
References 34 publications
(25 reference statements)
12
126
0
Order By: Relevance
“…This gives rise to a positive ionospheric storm (e.g., Buonsanto, 1999) whereby the TEC is also increased. As is expected, local uplifting of plasma and its re-distribution due to the eastward PPEF would have a certain time constant and has been observed by others also (Tsurtani et al, 2004;Bagiya et al, 2009). Therefore the first peak in VTEC occurs nearly after 1 h 45 min of the southward turning of the IMF B z .…”
Section: Longitudinal Variation Of Vtecmentioning
confidence: 72%
“…This gives rise to a positive ionospheric storm (e.g., Buonsanto, 1999) whereby the TEC is also increased. As is expected, local uplifting of plasma and its re-distribution due to the eastward PPEF would have a certain time constant and has been observed by others also (Tsurtani et al, 2004;Bagiya et al, 2009). Therefore the first peak in VTEC occurs nearly after 1 h 45 min of the southward turning of the IMF B z .…”
Section: Longitudinal Variation Of Vtecmentioning
confidence: 72%
“…The morphological features of TEC such as the diurnal, seasonal, latitudinal, and solar activity variations have been investigated by several workers using various techniques over different parts of the globe [Lanyi and Roth, 1988;Goodwin et al, 1995;Abdu et al, 1996;Davies and Hartman, 1997;Mannucci et al, 1998;Afraimovich et al, 2001;Brunini et al, 2003;Jee et al, 2005;Rama Rao et al, 2006;Bagiya Mala et al, 2009;Prasad et al, 2012]. One of the most important electrodynamical features of the equatorial ionosphere is the double-humped latitudinal distribution of ionization centered at the dip equator, which is popularly known as the equatorial ionization anomaly (EIA) [Appleton, 1946].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [81] found the EIA crest in TEC is maximum in equinox months constitute due to EEJ strength. The research of Rama Rao et al [39] reported that the positions of the EIA crest and its [26] found (r = 0.53) over the Brazilian region; Rama Rao et al [39] found (r = 0.62), Bagiya et al [44] found (r = 0.71) and Venkatesh et al [26] found (r = 0.51) in the Indian region stations. Our results agree with this study showing the positive relation between GPS-TEC and EEJ strength.…”
Section: Dependence Of Gps-tec On Eej Strengthmentioning
confidence: 96%
“…The plot in Figure 1 and Figure 2 states that the amplitude of the diurnal maximum is higher in the equinoctial months, which may be due to higher thermospheric [O/N 2 ] ratio and EEJ strength over the Surat station. It is normally accepted that the thermospheric neutral composition has a direct control on the seasonal variation of GPS-TEC [44] [50]. Oryema et al [51] and the references therein reported that, during the daytime in an equinoctial season, the sun is overhead the equator and temperature level at the equator are hotter than at the poles, therefore from the equator meridional wind flows towards the pole.…”
Section: Seasonal Variation Of Gps-tecmentioning
confidence: 99%